O fenômeno El Niño Oscilação Sul e a erosividade das chuvas em Santa Maria, RS - Paula, Gizelli Moiano de (2009)
A large-scale phenomenon that greatly affects the weather and the climate of different locations of the Globe and that has been widely studied during the last three decades is the El Niño Southern Oscilation (ENSO). ENSO leads to changes in the atmospheric circulation and affects climate variables, mainly rainfall, in all regions of Brazil. During El Niño years (the positive phase of ENSO), rainfall is often above normal in Southern Brazil whereas during La Niña years (the negative phase of ENSO), rainfall is often below normal. Some of the rainfall properties are affected by ENSO like frequency, intensity and amount. These properties are important to define if rainfall events are erosive. There are some methods of determining rainfall erosivity, among them the best and most used in Rio Grande do Sul State is the EI30 erosivity index. The objective of this dissertation was to determine and associate the EI30 erosivity index of rainfalls with the ENSO phenomenon in Santa Maria, RS, Brazil. Daily precipitation data recorded from 01 July 1978 to 30 July 2008 collected in a standard Climatological Station in Santa Maria, RS, were used. Individual erosive rainfall events were identified in the records, grouped into El Niño, La Niña and Neutral years, and had their EI30 calculated. Rainfalls were also grouped into three patterns: Advanced, Intermediate and Delayed. Pearson correlation and regression analyses between the EI30 erosivity index and the Niño Oceanic Index (NOI) were performed and the regression was tested with the t test in order to quantify the relationship between the two variables, aiming a possible predictability of the erosion potential of rainfall events from Sea Surface Temperature (SST) in the Pacific Ocean. Rainfall erosion potential in Santa Maria is affected by ENSO, so that a greater number of rainfall events have higher erosion potential during El Niño and neutral years. The variability of the rainfall erosion potential is greater during Neutral years than during years with SST anomalies. The frequency distribution of the EI30 erosivity index is skewed to the right in El Niño, La Niña and Neutral years. Rainfalls pattern is changed in years with SST anomalies, so that there is a slight increase in Advanced rainfalls during El Niño years and a slight decrease in Delayed rainfalls during La Niña years, whereas there is a decrease in rainfall events with Intermediate pattern during El Niño and La Niña years compared to Neutral years. The predictive capability of the erosion potential of rainfall events in Santa Maria from NOI index is weak or not possible.